The Impact of Health Education on Compliance to Screening Practices in Breast Cancer - Hamed, Basma Shokry; Abd El Bary, Nasser; Helmy Hebesh, Eman (Asian Pacific Journal of Cancer Care, 2025)
Background: Screening for breast cancer in asymptomatic women can lower the disease’s mortality rate and improve treatment outcomes. Increasing adherence to breast cancer screening programs is essential. Objectives: To estimate the current level of females’ awareness, attitudes, and screening about breast cancer and to evaluate the impact of health education on adherence to breast cancer screening practices. Methods: Between September 2023 and May 2024, 62 women were enrolled in a quasi-experimental intervention study at Menoufia University Hospital through the family medicine outpatient clinic. Medical history and demographics were gathered prior to the intervention. All patients also had their awareness, attitudes, and compliance with breast cancer screening assessed. The women were then divided into two groups at random: An intervention group, which included 28 women undergoing an educational program, and a control group, included 34 women. A month following the start of the health education program, the outcome measures were evaluated. Results: Statistically, no significant disparities between the intervention and control groups in average score of knowledge, attitude and any of the included practices or interest in a getting a screening mammogram, according to pre-intervention data. With regard to the control group, the post-intervention assessment revealed a significant rise in the intervention group’s practice of self-examination and mammography, as well as a higher level of interest in screening mammography. Conclusion: An effective strategy to identify and treat breast cancer early is to raise awareness of screening programs.